No Longer Neutral: The ECB’s Geopoliticization of the International Role of the Euro - Lukas Spielberger (Politics and Governance)
While the euro has, since its creation, been the world’s second most important currency, the ECB has long depoliticized the international role of the euro by proclaiming a neutral stance. However, as this article explains, since 2019, the ECB has embraced currency internationalization and framed the issue in geopolitical terms. This policy change reflects a response to a changed international political environment after 2018 and it has led the ECB to seek closer political coordination regarding external economic policy. As the international role of the euro has become a concern for the EU’s broader geoeconomic turn, it may, however, become difficult for the ECB to reconcile its political independence with its more geopolitical view of currency internationalization.